1988
DOI: 10.1111/j.1438-8677.1988.tb02133.x
|View full text |Cite
|
Sign up to set email alerts
|

Relations between mycorrhizas and fruitbodies of mycorrhizal fungi in Douglas fir plantations in The Netherlands

Abstract: SUMMARY Relations between above‐ground fruitbodies of mycorrhizal fungi and mycorrhizas in the soil were studied in 23 Douglas fir stands of various ages in The Netherlands. In the autumn of 1986, fruitbody and mycorrhiza density and diversity were determined. Quantitative relations were found between above‐ground fruitbodies of mycorrhizal fungi and below‐ground mycorrhizas. Mycorrhiza density explains fruitbody density better than mycorrhiza frequency, but fruitbody density is an unreliable estimator of myco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 8 publications
2
18
0
Order By: Relevance
“…Some authors (Jansen & de Nie, 1988 ;Termorshuizen & Schaffers, 1989 ;Jansen, 1991) observed a quantitative relationship between the total number of ECM fungal fruit bodies and the number of ectomycorrhizas in different conifer stands in The Netherlands. However, the response of below-ground fungal components to increased N availability cannot necessarily be deduced from fruit-body data, because there is growing evidence that above-ground fruit-body surveys do not accurately depict the qualitative structures of the below-ground ECM communities (Dahlberg & Stenlid, 1995 ;Taylor, 1995 ;Gardes & Bruns, 1996 ;Dahlberg, Jonsson & Nylund, 1997).…”
Section: Effects Of Varied N Treatments On Ectomycorrhizas In Plantatmentioning
confidence: 99%
“…Some authors (Jansen & de Nie, 1988 ;Termorshuizen & Schaffers, 1989 ;Jansen, 1991) observed a quantitative relationship between the total number of ECM fungal fruit bodies and the number of ectomycorrhizas in different conifer stands in The Netherlands. However, the response of below-ground fungal components to increased N availability cannot necessarily be deduced from fruit-body data, because there is growing evidence that above-ground fruit-body surveys do not accurately depict the qualitative structures of the below-ground ECM communities (Dahlberg & Stenlid, 1995 ;Taylor, 1995 ;Gardes & Bruns, 1996 ;Dahlberg, Jonsson & Nylund, 1997).…”
Section: Effects Of Varied N Treatments On Ectomycorrhizas In Plantatmentioning
confidence: 99%
“…Such genets may not fruit because of genetic sterility or low mycorrhizal colonization (Lamhamedi et al 1994;Selosse et al 1998b). The scarcity of Laccaria fruit bodies in mature plantations of Douglas fir, probably because of canopy closure (Jansen and de Nie 1988), is a further hindrance to Laccaria population assessment by basidiocarp surveys. Thus, molecular markers are necessary for detecting potential progeny of S238N on roots.…”
Section: Introductionmentioning
confidence: 99%
“…Arno Ids ( 1981) and Jansen (1981) did research on the mycoecology and mycosociology of heaths and oak forests in the Netherlands . Later, Jansen & De Nie (1988) investigated the relationship between mycorrhizae and the fruit bodies of fungi in plantations of Douglas fir. In North America, the yields of mycorrhizal and saprophytic fungi in coniferous forests have been studied by several researchers, such as Vogt et al (1980Vogt et al ( , 1981, Bills et al (1986), and Villeneuve et al (1989).…”
Section: Introductionmentioning
confidence: 99%